The Effect of Adding ZrO2-Cu Coating on the Physical Properties of Aluminium Matrix Composites - FLAEH, ABD AL-ALKAREEM; JASIM, NUHA HADI (Basrah Journal for Engineering Sciences, 2015)
In this study the powder metallurgy technique was used to prepare the composite materials using the aluminum powder as the basis metal, with the additions of the 2, 4 and 6%Wt. of ZrO2-Cu coating and mixing it manually for 15 minutes at (30-32 oC). Then the mixture are compacted at pressure 320 MPa and sintering at 640oC in the atmosphere furnace with argon gas protection. The physical properties include the green density, sintering density, porosity, and microstructure were examined for the prepared samples. X-ray analyzer was used to identify the phases changes in order to find the chemical reaction which it can be excepted occurred in the sintering samples. The result of X-Ray diffraction shows that there is new phase exist after sintering for all weight percentage.